Top 100 houses & landscapes. IV - JTart (China : JTart publishing & media, 2013)
As a professional Top 100 Houses and Landscapes IV Books that introduces designs on residential communities and landscape, it is a great sequel to the previous three volumes. It covers a good number of classical cases in various types, including high-rise, small high-rise, low-density, villa and mixed residential. Each category displays its own landscape and architectural style with valuable pictures and texts. Each project is introduced in a comprehensive way from features, profile, planning and layout, landscape design to housing design.
High-rise -- Neoclassical style -- Shanghai bay line, phase II -- Taicang green land town -- Guiha star city -- Modern style -- Shanghai government - subsidized housing -- shenzhen qiaoxiang village affordable housing -- fantasia mic plaza -- huizhou million city -- merchants yongjing bay -- phase I of shidai nansha shanhuhai -- lvhai bay gaden -- pengda moore town -- Eothen, beijing -- heheng urben plaza -- New chinese style -- Liuzhou shengtian dragon bay -- Spanish style -- Tianjin carme -- British style -- British Villa, chengdu -- European style -- Eastern garden foshan -- natong wanhao mansion -- Medium high -rise -- Neoclassical style -- Jinguang Residential area -- shanghai yangpu jiangwan -- Xianghe central leading mansion -- tengen taoyuan, nanjing -- xinyue garden, phase II, lianfa -- Modern style -- beijing sun blog residence community -- crape myrtle .upper town -- vanke golden homes, wuhan -- guangzhou new world golden lake phase 4 -- shanghai xinkai homeland residentaial area -- oct the rivera phase 7, shenzhen -- Luneng sanya bay beautiful town, sanya -- Ziyuan -- golden fragrant forest, Beijing -- Low - density -- Zhongyu l$1 (Bambassadeur residence -- poly xitangue -- 19th century AD belle time -- New chinese style -- Evian Vally -- Spanish style -- Dongguan Greenshade, Windsor castle -- spanish poetic cultural residence - Beijing Jinke patio phase one -- British style -- Leaves Whisper -- CSC palais grand - ducal ,New bay city in Shanghai -- Qingdao vanke red county -- rUIJING CROWN WATER Edge longyuan town -- French style -- royal spring villa, beijing -- herong renowned mansion, Nantong -- Greenland New Metropolis -- European style -- Suzhou little rock -- Wukuang hallstatt villas -- gemdale. international garden, wuhan -- Villa -- Modern style -- Nanchang Tianmu - junhu -- New chinese style -- vanke liangzhu bailu junxi residential Area -- Southeast Asian style -- Luneng sanya golf villa phase L -- American style Changsha - American stories -- French style -- gemdale Dongguan luxury nature -- European style -- peak villa, chengdu -- lake side -- ching shan hui valley -- Mixed -- Modern style -- ningbo yinzhou talent apartment -- New chinese style long island, chongqing -- purple greden , nanjing -- American style -- Dalian hungwei lanshan , phase I -- European style -- jintang. palm lake interational community, Chengdu s
Includes index.
engineering bookfair2016
Chinese and English.
Keywords: Architecture, Domestic -- Designs and plans -- China; Landscape design -- China